GEOTHERMAL ENVIRONMENT FOR NEO-VOLCANISM IN TRANS-CARPATHIAN TROUGH AND EAST SLOVAKIAN DEPRESSION - Kutas, R.; Majsin, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Heat flow values in the Pannonian basin may reach 50-60 mW/m2. Being anomalous for stable tectonic platforms, it may suggest a close relationship of Neogene-Quaternary volcanism to a source of geothermal activation. Magmatic products surge the amount of heat sufficient to melt substantial volumes of lower crust, but lava flows or its single intrusions in the upper layers of the crust cool down relatively quickly (within the first million years) and cannot provide considerably high heat flow for a long period. This can only be done by deep sources of heat and uplifting the heated mantle substance. The first phase of active volcanism in the region was related to the maximum temperature increase in the upper mantle, while the last one was associated with the beginning cooling process. Intrusions of Mesozoic bodies in volcanism, a high degree of metamorphism of Mesozoic deposits as well as high value of the heat flow within the Inner Carpathians (55-60 mW/m2) indicate a high geothermal activity. The depth of the boundary between the solid crust, which is dominated by the molecular mechanism of heat transfer, and a layer of partially molten material (where heat-mass transfer previously occurred) is evaluated to be 25-30 km. By Early Cenozoic a thermal mode had still not stabilized. Heat flux density reached 60 mW/m2, and the top of the asthenosphere was at a depth of 100-120 km, with crustal thickness making up 40 km. These facts and the intensity of the heat flow anomalies facilitate estimating maximum temperature in the foci of melting to reach approximately 1000-1100°C. The resulting estimates of temperatures and the depth in foci of melting conclude on a major role of volatile components (water and carbon dioxide, primarily), which is confirmed by explosive volcanism distribution. The second phase of volcanism is associated with cooling of melts, thermal immersion, and the formation of extension zones around mantle diapir, to be followed by decompression. Geothermal environment in the trans-Carpathian trough and the Inner Carpathians match the most up-todate explanation for the geodynamic evolution of the Carpathian region in the Neogene-Quaternary. Accordingly, large crustal massifs and extensive volumes of sediments and water plunged into the upper mantle resulting from the subduction of the Pennine sea basin, and the collisions of the Eurasian plate with a number of other microplates in the Inner Carpathian area. In the Mesozoic crustal material of the upper mantle was activated and heated enough to start melting at relatively shallow depths. The enrichment of the mantle with fusible elements and the fluids resulted in the overall decrease in melting temperatures. The formation of the mantle diapir was furthered by the extension of the crust, its submelting, and generation of sundry magma chambers. There occurred shrinking and alignments of the Earth's crust beneath all structures of the basin, regardless of their previous history.
Keywords: heat flow; magmatism; temperature; Pannonian basin